Plasmonic Photothermal Heating of Gold Nanoshell Solutions - Nga, Do Thi; Nam, Le Ba; Thao, To Thi; Duong, Vu Thi Thuy (Communications in Physics, 2020)
We present a theoretical approach to theoretically investigate how gold core-shellnanoparticles dispersed in water thermally respond to near-infrared-regime laser illumination. First, the absorption cross section of gold nanostructures is calculated using Mie theory. Second, we determine the absorbed power density when the solution is exposed by the laser light. Here, the solution of nanostructures is assumed to be uniform and homogenous. Third, we analytically solve the transient bioheat equation to calculate time-dependent temperature increase. Our theoretical calculations quantitatively agree with previous experiments without any adjustable parameter.This approach would provide a reliable tool to understand photothermal effects in unexplored structures.